ICC Court Decision on Reparation for Victims of the Post-Election Violence: No Reparation without Conviction Prosecutor v. William Samoei Ruto and Joshua Arap Sang, Decision on the Request Regarding Reparations, 1 July 2016 - Musiał-Budnicka, Joanna (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
On 1 July 2016, the Trial Chamber V(A) (Trial Chamber) of the permanent International Criminal Court (ICC) in its Decision on the Request regarding Reparations (Decision on Reparations), by majority held that the Trial Chamber cannot proceed further and decide on the reparation issues connected to the joint trial of Kenyan Deputy President William Samoei Ruto and co-accused, ex-journalist Joshua Arap Sang, both of whom faced charges of crimes against humanity for their suspected role in “post-election violence” that led to the deaths of approximately 1,000 persons and over 300,000 displaced persons. In its ruling, two of the three Trial Chamber judges, who terminated the Ruto and Sang case earlier on April 5, 2016, declined to consider the merits of the victims’ views and concerns expressed by the Legal Representative of Victims - Wilfred Nderitu (LRV). Therein, the LRV requested the Chamber (1) to establish that the Government of Kenya bears an obligation to provide reparations to victims of the post-election violence of 2007-2008 for various form of harm suffered and/or (2) to initiate and provide assistance for such victims through the Trust Fund for Victims (TFV) in accordance with its assistance programme. In other words, the LRV asked the Chamber to be part of the cause to award reparations and assist the victims of the 2007-2008 post-electoral violence in Kenya after collapse of the ICC’s Ruto and Sang case. The majority of the Trial Chamber in its ruling reasoned that due to the fact that the Ruto and Sang case was terminated on the Defence Motion on “No Case to Answer”, the Trial Chamber has no power to make any decision on the question of reparation in accordance to Article 75 of the Rome Statute for the benefit of the post-election violence victims. The Presiding Judge Chile Eboe-Osuji strongly dissented, explaining further his thinking on the question of reparations he provided earlier in the Reasons of Judge Eboe-Osuji. In his Dissenting Opinion, Judge Eboe-Osuji upraised a number of significant arguments supporting the view that the Court has legitimate power to address reparations for harm suffered to the victims as a result of crimes if such crimes have been found to have taken place but the persons standing trial for his participation in those crimes is not fund guilty. While the Dissenting Opinion of Judge Eboe-Osuji has no solid basis in the international criminal law documents,i n the eyes of the victims and the general public the majority Trial Chamber decision can be seen as the lost hope of being compensated for the suffered harm. This is due to the fact that the reparation principles arising from Article 75 (1) of the Rome Statute are based on the concept of individual criminal responsibility, rather than on the State’s responsibility. Nevertheless, one of the aims of this article is to emphasise that the reparations provisions contained in the Rome Statute and the Rules of Procedure and Evidence are vague and that no overarching guidelines exist to assist the different Trial and Appeals Chambers to conduct efficient reparations proceedings. The adoption of principles in the Ruto and Sang case could simply clarified to an extent the reparation process in that case, even when these principles would not necessarily apply to future cases. In such view, the majority decision is seen as a lost chance to clarify the law on the reparation issue in circumstances where the case was terminated on the no-case basis. In the lack of a specialised reparations Chamber, it is clear that the question of reparation following a trial (however concluded or terminated) falls to the Trial Chamber that conducted the relevant trial.
Keywords: Międzynarodowy Trybunał Karny; zadośćuczynienie; zbrodnie przeciwko ludzkości; Fundusz Powierniczy dla Ofiar; konkurencyjność Bloemers; globalna gospodarka oparta na wiedzy; Kuriata; indywidualne społeczeństwo